Enhancement of Intestinal Immune Function in Mice by β‐D‐Glucan from Aureobasidium Pullulans ADK‐34. (11th July 2013) - Tanioka, A.; Tanabe, K.; Hosono, A.; Kawakami, H.; Kaminogawa, S.; Tsubaki, K.; Hachimura, S.
Abstract β‐Glucans, glucose polymers that are the main constituents of the outer cell walls of micro‐organisms such as fungi and yeast, are known to play an immunostimulatory role. We prepared β‐glucan (β‐(1‐3), (1‐6)‐D‐glucan) from an edible cultured fungus through fermentation techniques using a strain of Aureobasidium pullulans ADK‐34. The purity of this β‐glucan preparation (AP‐FBG) was demonstrated to be high through various instrumental analyses. We then examined the effects of AP‐FBG on intestinal immune systems. We prepared Peyer's patch (PP) cells and measured interleukin (IL)‐5, IL‐6, and IgA production in culture media with AP‐FBG. We found that both cytokines and IgA increased; furthermore, IL‐6 secreted by PP dendritic cells (PPDCs) cultured in the presence of AP‐FBG significantly increased. We tested IgA production after oral administration of AP‐FBG for 2 weeks and found that AP‐FBG tended to promote the production of IgA in the small intestine. Interestingly, we observed a significant increase in IgA production in the small intestines of mice treated with cyclophosphamide (CY; an immunosuppressant) after oral administration of AP‐FBG diet compared with CY‐treated and control diet mice. Production of IL‐6 and IgA by PP cells and IL‐6 production by PPDCs in AP‐FBG‐fed and CY‐treated mice also increased. These results demonstrate that AP‐FBG has the ability to activate PPDC and induce IL‐6 production and IgA secretion in PP cells. These abilities were more clearly expressed when AP‐FBG was orally administered in a CY‐induced immunosuppressed condition. Therefore, AP‐FBG may be a useful ingredient for preparing functional foods with immunomodulatory activities.